Biomechanical factors of competitive success with the rotational shot put technique - Lipovsek, S.; Skof, B.; Stuhec, S.; Coh, M. (New Studies in Athletics, 2011)
The aim of this study was to determine the biomechanical parameters in the rotational technique that have the greatest impact on the distance achieved and thereby on competitive success in the shot put. The sample consisted of 10 top-level putters competing at the 2008 European Cup Winter Throwing in Split, Croatia; the best throw by each of the subjects was selected for examination.